Bioassay-directed isolation of quaternary benzylisoquinolines from Berberis integerrima with bactericidal activity against Brucella abortus - Gholamhassan Azimi; Ali Hakakian; Mustafa Ghanadian; Ali Joumaa; Saeed Alamian (Wolters Kluwer Medknow Publications, 2018)
Berberis integerrima Bonge. (Syn: Berberis densiflora Boiss. & Buhse) is a shrub widely distributed in Middle East and central part of Asia. An ethnobotanical study revealed that indigenous and tribal people in Iran use B. integerrima root decoction for treatment of brucellosis. Therefore, the aim of this study was bioassay directed isolation of antibacterial compounds from this plant based on their in vitro bactericidal activity against Brucella abortus. Briefly, the ethanol extract of B. integerrima was fractioned and subjected to preliminary antibacterial screening tests against Brucella. The more active fraction (Fr.3) was subjected to purification by repeated chromatography systems. Quaternary benzylisoquinoline alkaloids including columbamine, palmatine, berberine, and jatrorhizine were four main components identified in the selected active fraction. Except for berberine which is reported before, palmatine, columbamine and jatrorhizine are isolated for the first time from this plant. Anti-brucellosis properties of isolated compounds 1-4 were studied against B. abortus under different test conditions. In minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) results, jatrorhizine (4) showed more antibacterial activity with MIC and MBC of 0.78 and 1.56 μg/mL, respectively. In both agar well diffusion and disk diffusion ANOVA results showed that there were statistically significant differences between compounds 1-4 versus placebo in all of the tested concentration (P <0.001). In conclusion, all of four alkaloids showed potent antibacterial activity against B. abortus but jatrorhizine and columbamine with free hydroxyl group on C-3 or C-2 showed more activity than palmatine and berberine without any free hydroxyl group on their structures. The antibacterial effects of columbamine (15 μg/mL) and jatrorhizine (15 μg/mL) were comparative to streptomycin (10 μg/mL) as standard drug which candidate them for more pharmacological researches to find new antibacterial agents against brucellosis.